Determinación físico-química del agua potable que se consume en el campus universitario de la Universidad Nacional de Trujillo - Departamento “La Libertad”- Perú - Ulloa Guevara, Rosa Teresa (2019)
The present study aims to determine the Physical-Chemical Characteristics of drinking water consumed in the university city of the National University of Trujillo - Department "La Libertad" - Peru, with the purpose of verify if they agree with the parameters of quality. 22 samples of drinking water were analyzed, the turbidity was determined by the nephelometric method, color by the colorimetric method, smell and taste by the organoleptic method, temperature by the thermometric method, total solids by the evaporation method, pH by the potentiometric method, total alkalinity by the alkalimetry method, total hardness by the Versenate method, chlorides by the Mohr method, nitrates by the disulfonic phenol method and ammonia by the Nessler method. The results obtained are: turbidity 3,23 UTN; color, 6,6 UCV; smell and taste, acceptable; temperature, 21,17 ° C; total solids, 1292,6 mg / L; pH, 6,59; total alkalinity, 152,68 mg / L CaCO3; total hardness, 348,11 mg / L CaCO3; chlorides, 124,802 mg / L CL; nitrate and ammonia, negative. It can be concluded that drinking water for consumption in the University City is within the quality parameters